Molecular characterization of avian influenza viruses (H5N2, H5N8, H5Nx and H9N2) isolated from chickens and ducks in the South of Egypt 2020 – 2021 - Ali, Ahmed A.H.; Mansour, Shimaa; Hefeny, Sozun M.; Sultan, Serageldeen (Journal of Advanced Veterinary Research, 2024)
This study was conducted to investigate the epidemiological situation of avian influenza viruses (AIV) and the molecular identification of the different AIV subtypes circulating among chickens and duck farms in South Egypt. A total of 143 samples were collected from chicken and duck farms in Qena (n = 105) and Luxor (n=38) governorates during 2020. The organs and swabs were collected from diseased chickens and healthy ducks. The viruses were isolated in embryonated chicken eggs (ECEs) and their propagation was confirmed by hemagglutination test (AHT) and molecular detection of matrix gene by reverse transcription polymerase chain reaction (RT-PCR). AIV subtypes were identified by RT-PCR and specific primers. Phylogenetic analysis of sequenced partial H5, N2, and N8 genes was performed. The results revealed that 15 AIVs were subtyped to 2 H5N2, 2 H5N8, 8 H5Nx, and 2 H9N2. While an isolate could not be subtyped by used primers. The H5-based evolutionary tree of 4 isolates revealed their categorization with the 2.3.4.4b clade with close relation to H5N8 isolates from Egypt in 2021 and Kazakhstan in 2020. In conclusion, the occurrence of H5 and H9 viruses pays attention to a public health concern. Also, non-identified HxNx reveals a new AIV HA and NA subtype may be present among chickens.